(untitled) (International Journal of Architecture and Urbanism, 2023)
Tourism is one of the industries that can improve the welfare of the people in Â an area, one.of.which is heritage.tourism. Visits to heritage tourism are one of Â the fastest growing tourist activities, so heritage tourism is an asset that should Â be developed by each region. In heritage tourism, there is a place attachment. Â Place attachment is a bond made by humans with a place. One aspect of the Â formation of place attachment is the meaning of place. A historical tourist Â attraction that has a place attachment is the Rumah Balai Ujung Tanjung Â Tanjungbalai. This study aims to analyze aspects of the meaning of the place Â owned by Rumah Balai. The.research.method used in this.research is a Â concurrent mixedmethod. The results of the analysis carried out stated that the Â aspect of the meaning of the place owned by Rumah Balai Ujung Tanjung is Â still low and this can be improved by increasing aspects of physical Â characteristics and aspects of social interaction. So that it can increase the Â number of visitors who come.